Becoming a Professional Educator: Teachers’ Reflective Practices in Shaping Students’ Moral Character - Indah Sari (Sufiya Journal of Islamic Studies, 2023)
This study aims to analyze teachers’ strategies in shaping students’ moral character through their roles as role models, mentors, advisors, and inspirers at MTs Al-Jam’iyatul Washliyah. Employing a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews with Aqidah Akhlak teachers and students, as well as field documentation. The findings reveal that the integration of teachers’ roles as role models and mentors has a significant impact on students’ discipline in vertical worship practices (morality toward Allah SWT) and obedience to authority (morality toward teachers and parents). However, the study also uncovers a disconnection in horizontal behavior, where peer interactions and personal integrity still demonstrate tendencies toward deviant conduct due to external environmental influences and low self-resilience. Data analysis concludes that methods of religious habituation and contextual advice are effective in fostering ritual awareness, yet require further reinforcement in the teacher’s role as an inspirer to stimulate students’ intrinsic motivation. The implications of this study emphasize the necessity of synergy between teachers’ reflective practices and intensive collaboration with parents in order to bridge the gap between formal obedience and authentic character awareness. This research contributes to the development of a morality-based teacher professionalism model within the ecosystem of contemporary Islamic education.